Optimization in the recovery and quality of silver concentrate of the mining Pasivos Ambientales - Escobedo Remachi, George Emerson (2023)
The main objective of this research work was to optimize the recovery and quality of silver concentrates by means of flotation of the Pasivos Ambientales mining company, using statistical software with which the optimal values of the independent variables such as Collector Z -11 (Sodium Isopropyl Xanthate), pH water and flotation pH medium, after running a 23 factorial model with three replicates in the center, the following equations were determined.Silver Concentrate Quality = 185724.16-29473.9*pHwater – 26526.5*pHmedium + 23.4718*Colector + 4210.56*pHwater*pHmedium Silver Recovery = -12180.57+ 1942.94*pHwater + 1748.64*pHmedium + 127425*Colector -277.5625*pHwater*pHmedium According to equation, the quality of the concentrate was able to determine the optimal values of pH water 6.5, pH medium 7.1 and Collector Z-11 20% with a law of 620,119 oz/Tc.With the equation of the recovery could be determined the optimal values of pH water 6.1, pH medium 7.1 and Collector Z-11 20% with a recovery of 92.6934%.